A sunscreen UV filter disrupts energy homeostasis and impairs growth in the endangered living fossil Tachypleus tridentatus - Guangjin Li; Yiting Li; Xingda Lin; Shiyong Wang; Meijiao Yan; Yaoyao Chu; Chuihong Fang; Zhi Chen; Fengxiao Hu (Journal of Hazardous Materials, 2026)

Gibberellin induces rapid regeneration of juveniles from the Sargassum fusiforme holdfasts - Lin Luo; Dongya Bao; Congquan Gao; Xingda Sheng; Peng Jin; Xu Gao; Zengling Ma; Binbin Chen; Mingjiang Wu (Aquaculture, 2025)

Impact of Carbon and Nitrogen Assimilation in Sargassum fusiforme (Harvey) Setchell due to Marine Heatwave Under Global Warming - Xingda Sheng; Xiaojie Zuo; Lin Luo; Guanfeng Pang; Huawei Zhang; Kit Wayne Chew; Dongshun Fang; Binbin Chen; Mingjiang Wu (Global Change Biology, 2025)
Because of the rising global temperatures, Sargassum fusiforme (Harvey) Setchell, a commercially valuable seaweed, has experienced reduced yield and quality due to high temperatures from marine heatwave events. However, the mechanisms underlying the effects of heatwave stress on S. fusiforme remain unclear. In this study, the mechanisms of heatwave stress on the carbon and nitrogen assimilation processes in S. fusiforme were analyzed. These results indicated that heatwave stress, especially at 30°C for 12 days, significantly increased the levels of hydrogen peroxide (83%), malondialdehyde (84.7%), and relative conductivity (16.5%) in algae, which suggested an increase in algal damage. Morphologically, heatwave stress damaged the thylakoid structure and reduced the photosynthetic efficiency of algae and accumulated NADPH, ATP, and α‐ketoglutarate significantly, resulting in decreased content of mannitol, the photosynthetic product. Additionally, physiological and transcriptomic results revealed that heatwave stress inhibited the rate of nitrate absorption rate and the activities of the most enzymes associated with nitrogen accumulation, while significantly upregulating glutamate dehydrogenase (GDH), suggesting a crucial role for GDH in S. fusiforme 's adaptation to heatwave stress. In terms of amino acid composition, proline and alanine were the most sensitive to heatwave treatment. Moreover, under the natural heatwave environment simulation validation experiment, the algae showed the same physiological performance as under laboratory conditions. The results indicated that marine heatwave events increased oxidative damage in S. fusiforme and inhibited carbon and nitrogen absorption and assimilation, ultimately leading to negative effects on the growth of algae. Thus, in the context of rapid global warming exacerbating marine heatwave events, our study provides valuable insights for high‐temperature‐resistant breeding and ecological management in coastal aquaculture.

Temporal and spatial changes of major endogenous phytohormones during the regeneration of juveniles from Sargassum fusiforme holdfasts - Guanfeng Pang; Lin Luo; Lina Guo; Congquan Gao; Xingda Sheng; Zengling Ma; Binbin Chen; Mingjiang Wu (Journal of Applied Phycology, 2023)